Recent Development of Islamic Corporate Social Responsibility - Rini Setyaningsih; Doddy Setiawan (Faculty of Economic and Business, 2019)
This study aims to review the development of research related to Islamic corporate social responsibility in well-known international journals such as the past ten years. The research review based on 42 articles. The 40 articles in international journals, and two articles in nationally accredited journals from 2009 until 2018. The analysis technique used in this study is charting the field method. This study classifies sample articles based on topics, variables, and research methods. The results of the review indicate that the majority of researchers discuss topics other than antecedents, and the consequences are 29 articles, of which 7 of them specifically discuss the measurement of Islamic corporate social responsibility. The antecedent variable dominated by company size and SSB size that calculates for each of 3 articles and the most discussed consequence variable is the financial performance of 3 articles, while the most dominant method used by researchers is an analytical method that counts 18 articles.JEL Classification: G21, M41